COMPARISON OF MULTIPLE CAMERA SEMI-AUTOMATIC SYSTEMS AND GLOBAL POSITIONING SYSTEM (GPS) AS DIFFERENT PLAYER TRACKING SYSTEMS IN FOOTBALL - Gürcan Ünlü; Bayram Polat; Aytek Hikmet Güler; Anıl Işık (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi, 2018)
Global positioning systems (GPS) as a wearable technology and multiple camera semi-automatic systems are two most popular technologies which aim to reveal physical performance of the players in both training and competitions. These technologies may have also specific contents in terms of benefits, advantages or disadvantages, and some recent studies have revealed the differences between these technologies. This paper aimed to discuss these technologies with respect to their benefits to practical application in light of the literature. The overall reliability and validity is good for both system especially in distance covered (Buchheit et al., 2014), Multiple camera semi-automatic systems due to having to predict some soccer events (corner kick, free kick, goals, penalties etc.) and providing same data about opponent team can be more useful than GPS in match analysis. On the other hand, GPS player tracking technology may become more useful in monitoring training loads since this system works independently of camera. Both systems have some limitations such as poor accuracy in computing high intensity running, acceleration, deceleration, and constant motion errors however these technologies have been developing so further innovations may overcome the limitations.